Penggunaan multimedia interaktif untuk meningkatkan pemahaman konsep keliling dan luas bangun datar pada peserta didik kelas IV sekolah dasar - Mutiara Alma; Sri Marmoah; Hartono Hartono (Didaktika Dwija Indria, 2019)
The purpose of this research to improving the conceptual understanding of circumference and area of plane object for fourth grade students of Ta’mirul Islam Elementary School in the 2018/2019 academic year using interactive multimedia. This research was a Classroom Action Research (CAR), that consist of three cycles, each cycle includes two meeting. Subject and sorce data in this research were teacher and students of IV D, Ta’mirul Islam Elementary School. The research uses collection and teachnique through observation, interviews, test, and documentation. The data validity used in source triangulation and triangulation of data methods. The data analysis teachnique used is an interactive analysis model. The conclusion in this research are interactive multimedia that can improve the concept understanding of circumference and area of plane object for fourth grade students of Ta’mirul Islam Elementary School in the academic year 2018/2019.